Scientific publications about DNA structure-function and PCR technique in Costa Rica: A historic view (1953-2003) - Albertazzi, Federico J (2004)
The spreading of knowledge depends on the access to the information and its immediate use. Models are useful to explain specific phenomena. The scientific community accepts some models in Biology after a peri- od of time, once it has evidence to support it. The model of the structure and function of the DNA proposed by Watson & Crick (1953) was not the exception, since a few years later the DNA model was finally accepted. In Costa Rica, DNA function was first mentioned in 1970, in the magazine Biología Tropical (Tropical Biology Magazine), more than 15 years after its first publication in a scientific journal. An opposite situation occurs with technical innovations. If the efficiency of a new scientific technique is proved in a compelling way, then the acceptance by the community comes swiftly. This was the case of the polymerase chain reaction, or PCR. The first PCR machine in Costa Rica arrived in 1991, only three years after its publication.